The Union for the Mediterranean: A missed opportunity. The challenges in the region would require a fundamental revision of the existing framework - Daniela Schwarzer; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2008)
French President Nicolas Sarkozy's project of a Mediterranean Union, which would have involved only the countries bordering on the Mediterranean but not the entire European Union, has caused months of tensions, particularly between Germany and France. It was pressure from the German federal government that caused this initiative to be redefined at the March 2008 EU summit as a relaunch of the Barcelona Process and thus as a pan-European project. Yet, what has been missing thus far is a much-needed discussion about the existing and future challenges to EU Mediterranean policy. Evidence abounds that the current co-operation framework requires fundamen-tal revision: Symptoms include the persistent authoritarianism and uncompetitive economies along the southern rim of the Mediterranean, the difficulty to engage in multilateral security co-operation with these countries, new estimates of high environmental and terrorist risks, and of increased pressure from migration. However, there is a danger that the agreement found for the Union for the Mediterranean (UFM) will prove to be nothing more than a shallow compromise aimed at quelling the internal dispute within the EU. Instead, the EU should use this opportunity to make Mediterranean co-operation more coherent, flexible, and effective
Keywords: 320